Fire safety policy and procedure at government hospital : case study Hospital Raja Perempuan Zainab II / Muhamad Arif Roslin and Nadira Ahzahar - Roslin, Muhamad Arif; Ahzahar, Nadira (2018)
Fire safety management has an essential aspect that must be carried out to ensure building performance will be maintained for daily operations. In Malaysia, the fire safety aspects are very new but the numbers of cases involved in hospital building are higher. The fire cases in Malaysia at government hospital are issued by Fire and Rescue Department of Malaysia (FDRM) such as recent cases at fire Intensive Care Unit (ICU) of Hospital Sultanah Aminah, where fire occurred and the seven victims were trapped during the fire in the building. The study in fire safety aspects able to improve fire safety management practices at the government hospital. The objectives of the study are to determine the level of compliance with policy and the procedure that is applied at the Hospital Raja Perempuan Zainab II Kota Bharu. This study employed both quantitative and qualitative methods to obtain data. 50 respondents from hospital staff took part in the study as the survey respondents. The data were analysed using the Average Index Method. From the findings, five factors policy and procedure have been applied at the government hospital. The finding of this research stated that the most critical aspect is staff training. The ways to improve fire safety management practices at the hospital is they must ensure that technical training is conducted among hospital staff and the evacuation frequency need to be improved. In addition, it is found that government hospital needs to emphasize the five factors in policy and procedure to ensure that hospital has good practice in fire safety management.